2021
DOI: 10.29333/aje.2021.6113a
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation between Learning Motivation and Learning Outcomes on Mathematics Subjects in XII Science Class Senior High School 4 Bone

Abstract: Students experience problems related to low learning motivation, causing their mathematics learning outcomes to become low. The purpose of this study was to determine the relationship between learning motivation and learning outcomes on mathematics subjects in XII science class senior high school 4 Bone. The subjects in this study were 30 students of XII science class senior high school 4 Bone. The sampling technique in this research is cluster random sampling. The method used in this study is a quantitative m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 7 publications
(5 reference statements)
2
3
0
Order By: Relevance
“…It is known that 80.8% of respondents stated that the learning process carried out was not interactive and interesting which caused boredom. These results are in accordance with the research of Nugraha and Nugraha [19], that the factors that cause low student learning outcomes are the tendency for students to feel bored, lack of motivation and low interest in learning. In addition, 73.1% of respondents stated that the learning media used were too monotonous (package books and power points) and 42.3% of respondents thought that the way the teacher delivered the material was not interesting.…”
Section: Analysis Of Students' Problems and Needssupporting
confidence: 92%
“…It is known that 80.8% of respondents stated that the learning process carried out was not interactive and interesting which caused boredom. These results are in accordance with the research of Nugraha and Nugraha [19], that the factors that cause low student learning outcomes are the tendency for students to feel bored, lack of motivation and low interest in learning. In addition, 73.1% of respondents stated that the learning media used were too monotonous (package books and power points) and 42.3% of respondents thought that the way the teacher delivered the material was not interesting.…”
Section: Analysis Of Students' Problems and Needssupporting
confidence: 92%
“…In addition, the research results by Bahri and Corebima (2015) stated that learning motivation and metacognitive abilities affected students' cognitive learning outcomes. It is similar with the findings of Nugraha et al (2021), which explained that motivation was positively correlated with students' mathematics learning outcomes. It denotes that motivation plays a vital role in the learning process, and motivation is also crucial in the learning activity to encourage and facilitate student learning process in achieving the expected learning goals.…”
Section: B the Effect Of Learning Motivation On Mathematics Learning ...supporting
confidence: 90%
“…To test the theoretical assumptions mentioned above, previous studies have reported that learning motivation is related to students' mathematics achievement (El-Adl & Alkharusi, 2020;Ning, 2020;Nugraha, Nugraha, & Widyastuti, 2021). It was also reported that tutoring is also related to student achievement.…”
Section: Introductionmentioning
confidence: 97%